Inertial ratchet driven by colored Lévy noise: current inversion and mass separation. (15th May 2018) - Lü, Yan; Lu, Hong
Abstract: Transport of underdamped particles subjected to colored Lévy noise in an asymmetric periodic potential is investigated. Besides the competition between the long jumps and the noise correlation that leads to current inversion, the inertial effect is another important factor that can influence the transport behavior. Note that the critical correlation time at which the current inversion occurs depends on mass. This leads to the current reversals on varying mass and implies mass separation even in the absence of whatever additional load force. Additionally, we find that the region of allowed correlation times for mass separation moves toward a smaller value of with increasing Lévy index or noise intensity.